O jogo teatral para a formação continuada dos professores de arte da educação infantil: um estudo de caso nos Centros de Referência da Educação Infantil em João Pessoa - Matias, Eliete Fernandes (2016)
That research aimed to investigate the dramatic games as a teaching tool to child education Art teachers of João Pessoa - Paraíba, to answer next question: As art teachers make the connection between their experiences in theater games developed in its Continuing Education, with its practices in early childhood education? We studied the continued training of these professionals, the dramatic and theatrical play in the children's universe and we observed the theatrical game and your enjoyment in the group of art teachers of the kindergarten. The research was theoretically based on readings in internationally renowned authors addressing educational thematic related the teacher education, child psychology and specifically dramatic and theatrical games. In terms of methodology, it was held one Workshop theater games for a group of twenty five teachers. In the workshop, which was structured in six meetings, exercises were developed, theater games and traditional games, and the relevant ideas were transcripted, and discussed in this master’s dissertation. Promote workshops of theater games in the continuing education of teachers, according to reports of the teachers, gave them the opportunity to reflect from the game: the needs and characteristics of the different child development stages; the various educational possibilities presented in the game; and hypotheses, questions about the difficulties to educate children's with Art in the school. Thus, we conclude that the workshops of theater games are spaces of experimentation and research, uniting aesthetic education, imagination, role play and playfulness, to expand the possibilities for critical and creative acting of teachers in early childhood education.